Efektivitas Pemberdayaan Stakeholder Sekolah dalam Peningkatan Mutu Pendidikan di SMP Muhammadiyah 30 Sihepeng Kecamatan Siabu Mandailing Natal - Syahdenan, Syahdenan; Akrim, Akrim; Isman, Muhammad (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
This study aims to analyze the effectiveness of stakeholder empowerment (teachers, principals, students, and parents) in improving the quality of education at SMP Muhammadiyah 30 Sihepeng, Siabu District, Mandailing Natal. Using a qualitative approach and a case study form, the research involved all stakeholder components in SMP Muhammadiyah 30 Sihepeng. Data collection techniques are carried out through interviews and observations, by applying data triangulation techniques to minimize bias and test data validity. The results showed that the effectiveness of stakeholder empowerment is reflected through teachers' active participation in decision making, training and professional development, parental involvement, and community support. Supporting factors involve active teacher participation, professional development programs, parental involvement, and community support, while inhibiting factors consist of teacher nonparticipation, unavailability of resources, parental involvement, and resistance to change. Alternative problem-solving to improve the effectiveness of stakeholder empowerment includes increasing teacher participation through training and workshops, strengthening professional development programs, intensifying parental involvement with two-way communication and periodic activities, optimizing resources through audits and seeking additional funding, and developing joint initiatives with communities. This research contributes to the context of improving the quality of education at SMP Muhammadiyah 30 Sihepeng and can be a reference for policy makers, principals, teachers, and other stakeholders in developing effective strategies for empowering stakeholders in improving the quality of education.